The Romanian National Breast Reconstruction Program - Results and Conclusions after 5 Years - BEJINARIU Catalin Gheorghe; MARINESCU Silviu Adrian; ENESCU Mircea Dan (Modern Medicine)
The optimization of the breast reconstruction treatment protocols and the introduction of state-subsidized national programs are global priorities. The present paper presents the results obtained within the National Program of Breast Reconstruction at the „Bagdasar-Arseni” Emergency Clinical Hospital, highlighting the advantages and disadvantages of the surgical techniques used. Materials and Methods: The results obtained after 71 surgical interventions were used for the study. The methodology used involved the use of demographic data, patient history, and the description of the surgical methods and techniques that were used. Results: Among the main results, the paper highlights the fact that mammary reconstruction by using the ‘expander-implant’ surgical technique was 5 times more frequent than the „implant-myocutaneous flap” technique. Post-operative complications have been present in 57% of the patients who associate comorbidities. Breast reconstruction using the TRAM (transverse rectus abdominis muscle) flap was the rescue solution for severe complications. Conclusions: The TRAM flap was proven to be the best technique in the treatment of difficult cases. Carrying out these statistical analyzes related to projects of a national scale form the solid foundation of documented studies that bring a significant contribution to the development of the Romanian medical system.